IMPROVING THE MECHANISM OF ECONOMIC SUPPORT OF THE STATE IN THE EFFECTIVE USE OF FORESTRY LANDS - Berdieva Sarvinoz Abdumalikovna (Journals Park Publishing, 2025)
This article highlights the problems of effective use of forestry land in the Republic of Uzbekistan and the shortcomings identified during research on the issues of the current mechanism of economic support by the state. The article provides ways to improve the mechanisms for solving existing problems and providing economic support. The study requires an integrated approach that includes problems of economic support of Forestry, principles, methods, analyzes, practical examples and scientific solutions. In his scientific research, the researcher described the effective use of forestry land, considered Forestry problems and ways to solve it scientifically, used methods of economic support, analyzed the growth rates of the total volume of forestry products (services), developed the mechanism of economic support and discussed the implementation of the mechanism. Reflected the conclusions and scientific proposals on which the study was based.
Keywords: Forestry, the use of forestry land, legal problems, land problems, economic problems, environmental problems, products, income, scientific developments, the mechanism of economic support.